The Influence of Brand Awareness on Purchase Decision with Social Media as an Intervening Variable: Penelitian - Maryanta Maryanta; Selvi Yuliawati; I Nyoman Simpen; Dwi Zarlis; Ni Wayan Lia Apriani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to empirically analyze and examine the influence of profitability, leverage, and firm size on firm value, with dividend policy acting as an intervening (mediating) variable. In a dynamic and competitive financial market landscape, maximizing firm value remains the primary objective of corporate financial management to enhance shareholder wealth (Brigham & Ehrhardt, 2020). The proposed research methodology employs an explanatory quantitative approach using secondary financial data from publicly listed companies on the stock exchange (Hair et al., 2021). Hypothesis testing is executed through Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess both direct and indirect structural relationships among the constructs (Ringle et al., 2020). The conceptual framework is grounded in signaling theory, trade-off theory, and pecking order theory (Myers & Majluf, 1984; Spence, 1973). Theoretical synthesis reveals that profitability and firm size positively impact firm value, whereas leverage exerts a contingent influence based on the capital structure risk profile (Gitman & Zutter, 2015). Furthermore, dividend policy is demonstrated to partially mediate the relationship between financial performance, firm scale, and market valuation, reinforcing the signaling mechanism of dividend payouts to external investors (Bhattacharya, 1979; Lintner, 1956). The practical implications of this research provide strategic insights for corporate financial executives in tailoring capital structure and payout decisions to drive market appreciation.